Education, Teaching Methods and Techniques in the Early Years of Islam During the Era of Prophet Muhammad (SAW) - Rahman, Md. Mizanur (IJRDO- Journal of Educational Research, 2018)
The main objective of this study was to investigate the educational activities and the teaching methods and techniques in the early years of Islam during the prophetic era for developing our existing education system. Education was launched by the Prophet Muhammad who was not only the preacher of a new religion and the head of the new community, but also an effective teacher and an enthusiastic promoter of learning. Islam is a knowledge-based religion, a religion of the Book. Since Muslim civilization has religion as a unifying factor, it is naturally based on the Qur’an and the tradition (Hadith). As soon as the mosque became the place of worship, it also became the first school in Islam and the main place for spreading Islamic education. The early Muslims were devoted to the cause of education. Although theirs was an oral tradition, they began to wholeheartedly seek knowledge with great zeal and enthusiasm. They were influenced by the effective methods and techniques of teaching of prophet Muhammad(SAW). The Holy Prophet did His best to convey knowledge to the people using every possible method and technique. In this paper, those methods and techniques of Holy Prophet and the early Muslims’ educational activities are reviewed scholarly.